Investigation of the filling-overflow behavior of corrosion products in reinforced mortar - Zhao, Yuxi; Xu, Dandan; Wang, Yuzhou; Wang, Haiyu (Journal of Asian Concrete Federation, 2023)
The investigation of the filling-overflow behavior of corrosion products in concrete is important for accurately predicting corrosion-induced concrete cover cracking. This paper utilizes the ethylene diamine tetra acetic acid (EDTA) titration method to quantitatively study the iron content in each zone of corroded reinforced mortar specimens. Based on this, the proportion and distribution of corrosion products are analyzed. Results show that approximately 50% of the corrosion products are transported to the mortar and corrosion products show a transport pattern to the surrounding low-concentration area in mortar. The direction of ion invasion on the mortar specimen does not exhibit a significant impact on the transport of corrosion products, while both the geometric size and quality of the mortar specimen affect the transport of corrosion products. Furthermore, the proposed method employs EDTA titration to quantify the filling and overflow of corrosion products, providing a valuable approach for further experimental research.